STUDIES ON THRESHOLD CURRENT DENSITIES FOR CONVULSION OF FISH USING A SQUARE WAVE STIMULATOR - BISWAS, K P (Fishery Technology, 2025)
The threshold current densities and volltage tensions (body voltages) between the head and tail for bringing about distinct reactions in Salmo irideus, Cyprinus Carpio, Tinea tinea, Gasterosteus aculeatus and Salmo fario were studied. In C. carpio and T. tinea, absolute current densities required decreased with increase in length of fish. Threshold current densities for different reactions of fish increased with rise in water temperature and conductivity of surrounding medium except in case of T. tinea where low current densities were sufficient in higher conductivity of water. Impulse D. C. was superior to continuous D. C. Better effect was noticed in fishes in lower current densities when their bodies were parallel to the lines of current conduction.